Role of ducks in the transmission cycle of tick‐borne encephalitis virus?. Issue 2 (15th July 2020) - Michel, Friederike; Ziegler, Ute; Fast, Christine; Eiden, Martin; Klaus, Christine; Dobler, Gerhard; Stiasny, Karin; Groschup, Martin H.
Abstract: Tick‐borne encephalitis virus (TBEV), a member of the family Flaviviridae, is the most important tick‐transmitted arbovirus in Europe. It can cause severe illnesses in humans and in various animal species. The main mechanism for the spread of TBEV into new areas is considered to be the translocation of infected ticks. To find out whether ducks can function as a natural virus reservoir in addition to serving as passive transport vectors, we carried out an experimental TBEV challenge study to reveal their susceptibility and resulting pathogenesis. Nineteen ducks were inoculated subcutaneously with TBEV strain 'Neudoerfl' and monitored for 21 days. Blood, oropharyngeal and cloacal swabs were collected throughout the experiment and organ samples upon necropsy at the end of the study. All samples were tested for TBEV‐RNA by real‐time polymerase chain reaction. TBEV‐specific antibodies were determined by virus neutralization test and ELISA. Organ samples were examined histopathologically and by immunohistochemistry. The inoculated ducks did not show any clinical symptoms. TBEV‐specific RNA was detected in all brain samples as well as in a few blood and swab samples. Moreover, all challenged birds produced TBEV antibodies and showed a mild to severe acute to subacute necrotizing encephalitis. TBEV‐specific antigen was detected in the brain of 14 ducks by immunohistochemistry. The short and low viremic phases, as well as the low virus load in tissues, suggest that ducks should not be considered as reservoir hosts. However, due to the high antibody levels, ducks can serve as sentinel species for the detection of natural TBEV foci.